Effects of Elevated pCO2 on the Survival and Growth of Portunus trituberculatus - Lin, Weichuan; Ren, Zhiming; Mu, Changkao; Ye, Yangfang; Wang, Chunlin (Frontiers in Physiology, 2020)
Identifying the response of Portunus trituberculatus to ocean acidification (OA) is critical to understanding the future development of this commercially important Chinese crab species. Recent studies have reported negative effects of OA on crustaceans. Here, we subjected swimming crabs to projected oceanic CO2 levels (current: 380 μatm; 2100: 750 μatm; 2200: 1500 μatm) for four weeks and analyzed the effects on survival, growth, digestion, antioxidant capacity, immune function, tissue metabolites, and gut bacteria of the crabs and on seawater bacteria. We integrated these findings to construct a structural equation model to evaluate the contribution of these variables to the survival and growth of swimming crabs. Reduced crab growth shown under OA is significantly correlated with changes in gut, muscle, and hepatopancreas metabolites whereas enhanced crab survival is significantly associated with changes in the carbonate system, seawater and gut bacteria, and activities of antioxidative and digestive enzymes. In addition, seawater bacteria appear to play a central role in the digestion, stress response, immune response, and metabolism of swimming crabs and their gut bacteria. We predict that if anthropogenic CO2 emissions continue to rise, future OA could lead to severe alterations in antioxidative, immune, and metabolic functions, and gut bacterial community composition in the swimming crabs through direct oxidative stress and/or indirect seawater bacterial roles. These effects appear to mediate improved survival, but at the cost of growth of the swimming crabs.